THU0126 Evaluation of the Effect of Tofacitinib on Measured Glomerular Filtration Rate in Patients with Active Rheumatoid Arthritis. (10th June 2014) - Kremer, J.; Kivitz, A.; Simon-Campos, J.; Nasanov, E.; Tony, H.; Vlahos, B.; Hammond, C.; Bukowski, J.; Li, H.; Schulman, S.; Raber, S.; Zuckerman, A.; et al.
Abstract : Background: In the clinical development programme of the novel oral Janus kinase inhibitor tofacitinib for the treatment of rheumatoid arthritis (RA), small mean increases in serum creatinine (SCr) (<4 μmol/L least mean squares difference from placebo [PBO] for tofacitinib 5 and 10 mg twice daily [BID] at Month 3) were observed and which plateaued early. In studies to date, with up to 5 years follow-up on and over 12, 000 patient (pt)-years of exposure to tofacitinib, 1, 2 mean increases in SCr remain small (mean change from baseline <8.84 μmol/L). While <5% of pts discontinued per protocol for SCr increases greater than 50% above baseline, these increases were generally not associated with clinical events of renal failure. Objectives: To assess changes in measured glomerular filtration rate (mGFR) with tofacitinib relative to PBO in pts with active RA. Methods: In this double-blind, PBO-controlled, Phase 1 study (NCT01484561 ) RA pts were randomised 2:1 to one of two fixed sequences (Seq): Seq 1 received oral tofacitinib 10 mg BID in Period 1 (P1) then PBO BID in Period 2 (P2); Seq 2 received oral PBO BID in both P1 and P2. P1and P2 were 6-7 and 4-5 weeks in duration, respectively. Each pt underwent mGFR evaluations by iohexol serum clearance at 4 time points (run-in, pre-dose 1 in P1, end of P1, and end of P2); estimated GFR (eGFR) was calculated using the Cockcroft-Gault equation. The primary endpoint was the geometric mean change in mGFR from baseline to end of P1. Secondary endpoints included the geometric mean change in mGFR from baseline to end of P2 and from end of P1 to end of P2; change in eGFR and SCr; RA clinical efficacy and safety. Results: 148 pts were randomised to Seq 1 (N=97) and Seq 2 (N=51). Baseline characteristics were similar between groups. In Seq 1, tofacitinib treatment in P1 was associated with a reduction of 8% (90% confidence interval [CI]: 2%, 14%) from baseline in geometric mean mGFR vs Seq 2. The reduction in geometric mean mGFR associated with tofacitinib in P1 reversed on PBO in P2, and there was no difference vs Seq 2 in the adjusted geometric mean fold change of mGFR at the end of the study (Seq 1:Seq 2: 1.04; 90% CI: 0.97, 1.11). However, from P1 to P2 there was a 5% reduction (90% CI: 1%, 10%) in mGFR in Seq 2 (PBO). eGFR and SCr showed similar changes to mGFR in Seq 1 but remained constant in Seq 2 (Table). Clinical efficacy and safety were consistent with prior studies. Conclusions: This study suggests that small mean increases in SCr and mean decreases in eGFR in pts with RA treated with tofacitinib occur in parallel with small mean decreases in mGFR, and that changes in these parameters with short term tofacitinib treatment appear reversible after discontinuation. Safety monitoring will continue in ongoing and future clinical trials and routine pharmacovigilance. References: Isaacs JD et al. Ann Rheum Dis 2012; 71 (Suppl 3): 672. Wollenhaupt J et al. Arthritis Rheum 2013; 65(Suppl 10): S993. Acknowledgements: This study was sponsored by Pfizer Inc. Medical writing support was provided by AM Reid, PhD, of CMC and funded by Pfizer Inc. Disclosure of Interest: : J. Kremer Grant/research support: Pfizer Inc, Consultant for: Pfizer Inc, A. Kivitz Grant/research support: Pfizer Inc, Consultant for: Pfizer Inc, Speakers bureau: Pfizer Inc, J. Simon-Campos: None declared, E. Nasanov: None declared, H. Tony: None declared, B. Vlahos Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, C. Hammond Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, J. Bukowski Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, H. Li Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, S. Schulman Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, S. Raber Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, A. Zuckerman Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, J. Isaacs Grant/research support: Pfizer Inc, Consultant for: Pfizer Inc DOI: 10.1136/annrheumdis-2014-eular.2492